2017
DOI: 10.15253/2175-6783.2017000400018
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture and pregnancy: oriental medicine as an ally in the treatment of low back pain

Abstract: Objective: to identify scientific evidence in the literature on the effect of acupuncture for the relief of low back pain during pregnancy. Methods: this is an integrative literature review. The bibliographic survey included articles indexed in the portal of six databases, using controlled keywords. Results: seven articles published in English were included. The studies using acupuncture for low back pain have been successful in reducing pain, as well as increased mobility, improved sleep, a sense of well-bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Mood swings observed during gestation may be attributed to variations in hormones, specifically estrogen and progesterone, which are at a higher level compared to non-pregnant women. 17 A systematic review of 714 studies conducted in Canada has found that one of the most frequent mood disorders in this period is depression, with a prevalence of 7.4% in the first trimester, 12.8% in the second trimester and 12.0% in the third trimester. 17 The increase in patience was highlighted among the reports, as 80% of pregnant women claimed improvement in this aspect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mood swings observed during gestation may be attributed to variations in hormones, specifically estrogen and progesterone, which are at a higher level compared to non-pregnant women. 17 A systematic review of 714 studies conducted in Canada has found that one of the most frequent mood disorders in this period is depression, with a prevalence of 7.4% in the first trimester, 12.8% in the second trimester and 12.0% in the third trimester. 17 The increase in patience was highlighted among the reports, as 80% of pregnant women claimed improvement in this aspect.…”
Section: Resultsmentioning
confidence: 99%
“…17 A systematic review of 714 studies conducted in Canada has found that one of the most frequent mood disorders in this period is depression, with a prevalence of 7.4% in the first trimester, 12.8% in the second trimester and 12.0% in the third trimester. 17 The increase in patience was highlighted among the reports, as 80% of pregnant women claimed improvement in this aspect. Some specific acupoints contribute to this positive percentage, as the shemen auricular point can lead to body relaxation, patience, and, in addition to analgesic and anti-inflammatory effects, also has sedative effects.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 12 articles included in this review the most cited professional was the nurse 9,11,[13][14][15][16]18 . ICHP are reaffirmed as a specialty of Nursing by the 581 Resolution of 2018 of the Conselho Federal de Enfermagem (COFEN -Federal Council of Nursing), which ensured for these professionals actions and research development in the general field of ICHP 26 .…”
Section: Professionals Who Use Ichp In Pregnant Women With Back Painmentioning
confidence: 99%
“…As a matter of fact, studies conducted around the world and in Turkey show that nurses also take an active role in T&CM treatments. [6][7][8][9][10][11] The World Health Organization (WHO) defines traditional medicine as "The sum of knowledge, skills, and practices based on theories, beliefs, and experiences specific to different cultures in the prevention, diagnosis, treatment, health protection, and improvement of physical and mental illnesses." 12 The terms "complementary medicine" or "alternative medicine" are used in many countries instead of traditional medicine and refer to practices that have not been integrated into the country's existing health system and have not become part of the country's culture.…”
Section: Introductionmentioning
confidence: 99%